'Enormous Opportunities' and 'Hot Frontiers': Sub-Saharan Africa in U.S. Grand Strategy, 2001-Present. Issue 1 (2nd January 2020) - Ryan, Maria
Abstract: This article argues that, in the 21st century, there has been a significant turnaround in the US approach to Sub-Saharan Africa. No longer is the region viewed solely as the site of human tragedy and internal wars where Washington has no tangible interests. Instead, US policymakers have increasingly viewed this part of Africa as a site of valuable commercial, geopolitical, and security interests—with particular emphasis on petroleum reserves, the market potential of its growing population, and its apparent locus as a site of transnational Islamist terrorism. Sub-Saharan Africa is now considered in grand strategic terms. Unintended consequences of US intervention are already visible, however; as it integrates the region into its global strategic calculus, the United States has begun to repeat mistakes made in other key regions of the world.